Argonaute-based dual lateral flow test for SARS-CoV-2 and influenza a virus - Xingyu Ye; Zhonglei Li; Zhengwei Fang; Nan Shen; Yani Zhang; Hanming Wang; Yi Liu; Yuanjie Zhou; Shanshan Fan; Peng Sun; Yue Zhong; Qian Liu; et al. (Sensors and Actuators Reports)
The lateral flow test (LFT) is crucial for community screening and early warning of infectious pathogens due to its portability and simplicity. However, antigen-based LFTs have relatively low sensitivity, while nucleic acid-based LFTs are limited in specificity and multiplexing capabilities, thus requiring improvements in accuracy and efficiency. In this study, we developed a dual lateral flow assay utilizing a thermophilic Argonaute, enabling the detection of multiple nucleic acids on a single strip with a sensitivity of 3 copies/μL and high specificity. Clinical validation showed 100 % concordance with commercial RT-qPCR results. This method not only preserves the high sensitivity of nucleic acid detection but also provides the benefits of portability, dual-target detection, and visual readout, highlighting its potential for point-of-care applications.